A remarkable new species of Paraclius Loew from Brazil (Diptera: Dolichopodidae) - Capellari, Renato Soares (Zootaxa, 2013)
The dolichopodine genus Paraclius Loew (Diptera: Dolichopodidae) presently includes over 150 described species worldwide and about 60 from the Neotropics (Yang et al. 2006; Capellari & Amorim 2009). Nevertheless, the genus was recovered as a polyphyletic assemblage of different lineages by Brooks (2005), and splitting of Paraclius into new genera will probably be required in the future to accommodate these groups. Particularly, some Neotropical species of Paraclius seem to be closely related to the genus Cheiromyia Dyte, based on the possession of an enlarged sperm pump that is folded back on itself (Brooks 2005; Brooks et al. 2010; Capellari & Amorim 2009), a character regarded by Brooks (2005) as a uniquely derived feature among the dolichopodines. Further studies of those species of Paraclius are needed to verify if they evolved as a grade within a group including Cheiromyia, or if establishment of a new genus for them is warranted.